You are on page 1of 10

# du u

I18  a2  u2 =
sin 1
a
c

du 1 u
I19 a 2
 u2 = a
tan 1  c
a

1 u
du sec 1  c
u u2  a2
a a

I20 =

dx
49.  9  x2

a2= 9 u2= x2

a= 3 u=x

du= dx

u
sin 1 c
= a

x
sin 1 c
= 3

dx
50.
 4 x 2

a2= 4 u2= x2
a= 2 u=x

du= dx

1 u
tan 1  c
= a a

1 x
= tan 1  c
2 2

dx
51. x x 2 16

a2= 16 u2= x2

a= 4 u=x

du= dx
1 u
sec 1  c
= a a

1 x
=
sec 1  c
4 4

dy
52.
 25  y 2

a2= 25 u2=9y2

a= 5 u=3y

3du= dy

du
3
= a  u2
2

1 u
tan 1  c
= a a

3 1 3 y
tan c
= 5 5

e x dx
 1  e2 x 53.

## a2= 1 u2= e2x

a= 1 u=ex

du= dx

u
sin 1 c
= a
sin 1 e x  c
=

dx
54.
 1  x  x

a2= 1 u2= x

a= 1 u=√x

1 12
x dx
du = 2

1
dx
2 x du=

dx
2du=
x
1 u
tan 1  c
= a a 2 ·

2 tan 1 x  c
=

dx
 2 x  x 2 55.

dx
 
 x  2x  1 1
2
 
=

dx
 1  x  1
2 =
a2= 1 u2= (x-1)2

a= 1 u= x-1

du= dx

u
sin 1 c
= a

sin 1 ( x  1)  c
=

dx
x 2
 x  2 56.

dx
 (x 2
 x  14 )  2  14 =

dx
 (x 2
 12 )  74 =

( x  12 ) 2
a2=` u2= 7
4

2
7 x  12
a= u=

du=dx

3x  1
57.  2x 2
 2x  3
dx

2x2  x  3
u=

du= (4x+2)dx

3
4
4 x  2 3x  1
 3x  3 2

5
2

4x  2
=
3
4  2x 2
 2x  3  52 
dx
2x  2x  3
2

du dx
3
  54  2
=
4
u x  x  32

dx
3
ln( 2 x 2  2 x  3)  54 
=
4
( x  x  14)  3 2  14
2

dx
3
ln( 2 x 2  2 x  3)  54 
=
4
(x  2 ) 2  5 4 1

2
5
4
2
( x  12 ) 2
a= u=

5
2 x  12
a= u=

du= dx

du
3
ln( 2 x 2  2 x  3)  54  c
a  u2
4 2
=

3
4 ln( 2 x 2  2 x  3)
=

x  12
 tan
1
 54  2
c
3
4 ln( 2 x 2  2 x  3) 5
2
5

x  12
 tan
1
 5
c
ln( 2 x 2  2 x  3)
3 2 5
4 2
=

2x 1
 tan
1
 2
5
c
3
4 ln( 2 x 2  2 x  3) 5
=

1
(1  x)dx

2

58. 0
1 x2

1 x2
u=

du  2 xdx

2 2

du
  xdx
2

1
dx 1
xdx
 
2 2

= 0
1 x 2 0
1 x2

a2= 1 u2= x2

a= 1 u= x-1

du= dx

b du 1 b du
= a
a2  u2

2 a u 2

(sin 
b
 12
-1 u
a )  (u1
2 du ) a

= l
(sin 
b
)  (u 2 du )
-1 u 1

a a

= l
(sin 
1
2
-1
x)  ( 1  x ) 2
0

= l
=
(sin -1 1
2 
)  ( 1  1 2 2 )  sin 0  1

 3
   1
 6 2
=

= 0.39

59.
4 dx
61.
2
x x 1

a2= 1 u2= x

a= 1 u=√x

dx
du= 2 x

dx
2du= x
4 dx
2
x  x x 1
=

b du
2
= a
u u2  a

4
2 sec 1 x
2

= l
2(sec 1 4  sec 1 2 )
=

2( 3  4 )
=

= 6